2015
DOI: 10.5812/ircmj.18976
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Occupational Accident Fatalities and Injuries Among Male Group in Iran Between 2008 and 2012

Abstract: Background:Because of occupational accidents, permanent disabilities and deaths occur and economic and workday losses emerge.Objectives:The purpose of the present study was to investigate the factors responsible for occupational accidents occurred in Iran.Patients and Methods:The current study analyzed 1464 occupational accidents recorded by the Ministry of Labor and Social Affairs’ offices in Iran during 2008 - 2012. At first, general understanding of accidents was obtained using descriptive statistics. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 27 publications
4
10
0
5
Order By: Relevance
“…Ling et al [58] reported that high-rise construction in CBD areas recorded a high number of fatal accidents. Dumrack et al [64] noted that projects located in the CBD and outer suburbs further from the CBD, represented largely fatal accidents than those on inner suburbs.…”
Section: Administrative Area In Which the Accident Occurredmentioning
confidence: 99%
“…Ling et al [58] reported that high-rise construction in CBD areas recorded a high number of fatal accidents. Dumrack et al [64] noted that projects located in the CBD and outer suburbs further from the CBD, represented largely fatal accidents than those on inner suburbs.…”
Section: Administrative Area In Which the Accident Occurredmentioning
confidence: 99%
“…A globalização e a implementação das novas tecnologias no labor têm provocado mudanças importantes que envolvem a relação entre o trabalho e o trabalhador, como o processo e jornada laborais, competitividade, entre outras, que interferem diretamente na saúde dos trabalhadores 1,2 . Nos países capitalistas, percebe-se um aumento da produtividade dos trabalhadores sem, muitas vezes, considerar os impactos que isto poderá desencadear na saúde das pessoas, tanto de ordem física quanto de ordem mental 2,3 .…”
Section: Introductionunclassified
“…Nos países capitalistas, percebe-se um aumento da produtividade dos trabalhadores sem, muitas vezes, considerar os impactos que isto poderá desencadear na saúde das pessoas, tanto de ordem física quanto de ordem mental 2,3 . De acordo com a Organização Internacional do Trabalho (OIT) cerca de dois milhões de pessoas em todo o mundo morrem durante o trabalho todos os anos 1 . Os acidentes de trabalho geram numerosas consequên-cias para a saúde dos trabalhadores, visto que impactam a integridade biológica do indivíduo e provocam aumento nos custos do sistema previdenciário e baixa produtividade laboral 1 .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The Indonesian government emphasized the importance of OHS in the workplace because work accidents not only lowers labor productivity, but also causing death (Delgado et al, 2015;Alizadeh et al, 2015).…”
mentioning
confidence: 99%